The achievement of the universal literacy in the High Nervion (Basque Country) - Merino Zulueta, Aketza (Historia y Memoria de la Educación, 2019)
The aim of this article is to study a concrete example of the literacy process in the Basque region of High Nervión, located between Araba/Álava and Bizkaia. In order to avoid generalizations and to highlight nuances, in the article we evaluate the achievements of the region by means of a comparison with other nearby areas as well as the rest of Spain. We go about our comparison in the context of studies based on the analysis of the access to the basic education as a way of improving human capital, education being a necessary factor but not in itself enough to initiate economic development. This aspect is dealt with in the first part of the work. Secondly, we will move from the first information on literacy that appears in the middle of the 19th century forward to 1935, just before the Spanish Civil War, when the High Nervión had recently achieved full literacy of all of its inhabitants. This occurred after a phase characterized by an economic and demographic crisis. The study was carried out on the basis of statistical sources such as municipal registers of inhabitants, in which the literacy skills of each person are noted. In the end we conclude that, despite important differences between territories, genders and labor situations, the literacy process was completed before the Civil War, enabling and empowering the human capital of the High Nervión’s for the economic development that the region was initiating.